Molecules of emotion : Why you feel the way you feel - Pert, Candace B. frey50 (New York Scribner, 2003)
Why do we feel the way we feel? How do our thoughts and emotions affect our health? Are our bodies and minds distinct form each other or do they function together as parts of an interconnected system?
ch. 1. The receptor revolution : an introductory lecture -- ch. 2. Romance of the opiate receptor -- ch. 3. Peptide generation : a continued lecture -- ch. 4. Brains and ambition -- ch. 5. Life at the palace -- ch. 6. Breaking the rules -- ch. 7. The biochemicals of emotion : a continued lecture -- ch. 8. Turning point -- ch. 9. The psychosomatic network : a concluding lecture -- ch. 10. Child of the new paradigm -- ch. 11. Crossing over, coming together -- ch. 12. Healing feeling -- ch. 13. Truth.
Keywords: Emotions; Neurochemistry; Medicine, Psychosomatic; Mind and body; Psychosomatic Medicine; Mind-Body Relations (Metaphysics); Esprit et corps